Strengthening Global Halal Supply Chains Through Shariah-Compliant Governance and Digital Traceability: Challenges and Strategic Opportunities in a Globalized Economy - Hussain, Mujahid (CV. SPDF Harmony, 2025)
Background: The expansion of global trade has positioned halal supply chains as a critical pillar in Islamic economic systems, particularly as Muslim and non-Muslim markets increasingly demand products that meet rigorous Shariah standards. Yet, the complexity of cross-border logistics, inconsistent certification practices, and frequent incidents of fraud continue to challenge the credibility and governance of halal value chains in the global market. Aims: This study aims to examine the structural challenges facing global halal supply chains while identifying strategic opportunities for strengthening Shariah-compliant governance. It specifically evaluates how ethical principles, regulatory harmonization, and digital traceability technologies can collectively enhance the resilience and legitimacy of halal logistics. Method: The research adopts a qualitative analytical approach informed by literature synthesis, regulatory review, and expert perspectives. Islamic economic principles serve as the interpretive foundation, enabling an assessment of both operational practices and their alignment with Shariah requirements. Result: The findings reveal three dominant challenges: fragmented certification standards, persistent cross-contamination risks, and widespread mislabeling driven by weak oversight. At the same time, globalization has created new opportunities, including broader market integration, rising ethical consumerism, and the use of blockchain-based traceability systems that improve transparency and reduce fraud. Conclusion: The study concludes that the long-term sustainability of halal supply chains depends on embedding Shariah-compliant governance within every stage of production, certification, and distribution. Strengthening mutual recognition frameworks among regulatory bodies, expanding digital verification tools, and enhancing stakeholder accountability are essential for restoring trust in global halal trade. When combined, these elements create a coherent pathway for building a transparent, ethical, and competitive halal economic ecosystem capable of meeting both contemporary global demands and core Islamic values.